PENGARUH PERENDAMAN DALAM CAMPURAN LARUTAN GARAM DAN EKSTRAK JAHE TERHADAP KANDUNGAN LEMAK DAN PROTEIN TELUR AYAM RAS - Nur Hafid; Ahmad Taufiq (Jurnal Ilmiah Fillia Cendekia, 2017)
The aim of this research was to find influence soaking in a mixture of salt solutions and ginger extract against a fat and protein contain of egg.This study was conducted in the laboratory of animal husbandry, Faculty of Agriculture, Kadiri Islamic University on 20 -26 June 2014 and eggs sample were analyzed the fat and the protein contain in the laboratory of biochemistry, MIPA Faculty, UMM on 27-30 June 2014. Methodology of this research used was the factorials method Completed Random Design (RAL). Research factors includes: immersion in a solution of salt, consisting of 2 level: G0: without additional salt; G1: by the addition of 15 %salt and factors soaking in ginger extract, consists of 4 level: J0: without additional ginger extract; J1: by the addition of 5% ginger extract, J2: by the addition of 10% ginger extract; J3: by the addition of 15% ginger extract.The total number of eggs required in this study was 96 egg. The results of the analysis showed that treatment of soaking in a mixture of salt solutions and ginger extract produce a fat and protein content of eggs with no significant different (P>0.05). The average of fat content (%) in each combination treatment: G0J0= 12,582 ± 0,160 ; G0J1= 11,782 ± 0,390 ; G0J2= 11,568 ± 0,331 ; G0J3= 10,894 ± 0,339 ; G1J0 = 12,640 ± 0,176 ; G1J1= 11,971 ± 0,142 ; G1J2= 11,392 ± 0,132 ; G1J3= 10,557 ± 0,473. The average of protein content (%) in each combination treatment: G0J0= 14,566 ± 0,218 ; G0J1= 14,651 ± 0,180 ; G0J2= 14,825 ± 0,098 ; G0J3= 15,003 ± 0,055 ; G1J0= 14,681 ± 0,075 ; G1J1= 14,909 ± 0,055 ; G1J2= 15,033 ± 0,082 ; G1J3= 15,062 ± 0,047. The conclusions of this research was not significantly different (P>0,05) use a mixture of salt solutions and dosage ginger extractin soaking egg against a fat and protein content.Suggested should be used combination treatment immersion in a solution of salt and 15% ginger extract to maintain a fat content and protein of egg and further investigation to determine the level of consumer test (organoleptic) of egg who received treatment in a solution of salt and ginger extract